The Role of Supply Chain Management on Operational Performance and Competitive Advantage as Intervening Variables at Tofu Factory in Malang Raya - Guntur Putra Mahendra; Muhammad Jihadi; Kenny Roz (Universitas Muhammadiyah Malang, 2021)
This study aims to determine the role of supply chain management on operational performance and competitive advantage as an intervening variable in a tofu factory in Malang Raya. The population in this study consists of 14 companies spread across Malang Raya with a total of 91 respondents. This research is a quantitative research using the WarpPLS 7.0 application. The data analysis technique used is using hypothesis testing and the Sobel test. The results test indicate that supply chain management has a positive effect on operational performance by mediating competitive advantage (full mediation). While supply chain management has a negative effect on operational performance if it is not through the competitive advantage variable.